Surface morphology of CuFeS2: The stability of the polar (112)/((112)over-bar) surface pair - Chen,VH-Y; Mallia,G; Martinez-Casado,R; Harrison,NM (Physical Review B, 2015)
The reconstruction and energetics for a range of chalcopyrite (CuFeS2) surfaces have been investigated using hybrid-exchange density functional theory. The stable nonpolar surfaces in increasing order of surface energy are (110), (102), and (114). In addition, the polar (112)/(112¯¯¯¯¯) surface pair was found to be remarkably stable with a surface formation energy that is only slightly higher than that of the (110) surface. The stability of (112)/(112¯¯¯¯¯) can be attributed to a combination of geometric and electronic mechanisms that result in the suppression of the electrostatic dipole perpendicular to the surface. Defect formation is a third mechanism that can further stabilize the (112)/(112¯¯¯¯¯) surface pair to an extent that it is thermodynamically preferred over the (110) surface. The stability of (112)/(112¯¯¯¯¯) means that regardless of the growth conditions, (112) and (112¯¯¯¯¯) facets are expected to have a significant presence in the surface morphology of CuFeS2.